Awareness/ Knowledge and practice about the cross-contamination control among Demonstrators - Farheen Malik, Muhammad Shoaib, Muhammad Ali, Javeria Afzal, Nida Badar, Rabia Mahmood, Mustafa Sajid (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Cross infection is a type of infection which can spread between three stack holders of the community i.e. Doctors, paramedical staff and the patient. The infectious diseases can spread from doctors to the patients, or patients to the doctors and healthcare workers2.These infectious diseases can spread during medical, surgical or dental treatment. Dental treatment is considered as most notorious one to spread cross infection between the healthcare workers and the community. Aim: To assess & check the awareness/ knowledge and practice about the cross-contamination control among demonstrators Study design: Descriptive Cross-sectional study Place and duration of study: Multan Dental College Multan. Duration of this study was 3 months. Methodology: This study was a cross-sectional survey which was conducted in the dental section of Multan Medical and Dental College Multan where forty demonstrators were included in the study. Data was collected by random sampling. After taking informed consent a questionnaire was filled by the participants. Results: Out of forty demonstrators. Males were twenty-fourwhile females were sixteen. 95% participants consider that the dental clinics/hospitals are additionally predisposed to contamination/infection when compared with other medical fields. 90% participants wash hands regularly after giving the treatment to each and every patient. Conclusion: Participants showed acceptable awareness/knowledge and satisfactory practice about contamination control. Keywords: Cross-contamination control, Demonstrators, Dentistry, and Protective measures